Soil carbon pools are affected by species identity and productivity in a tree common garden experiment - Waring, Bonnie G.; Smith, Kenneth R.; Belluau, Michael; Khlifa, Rim; Messier, Christian; Munson, Alison; Paquette, Alain (Frontiers in Forests and Global Change, 2022)
The formation and turnover of soil organic carbon (C), the largest terrestrial C pool, is strongly impacted by the ultimate source of that C: leaves, wood, roots, and root exudates. The quantity and quality of these inputs is determined by the identity of the plants involved. Yet substantial uncertainty surrounds the complex relationships among plant traits and soil C, precluding efforts to maximize whole-ecosystem C uptake in nature-based climate mitigation scenarios. In this study, we leveraged a biodiversity-ecosystem function experiment with trees (IDENT) to explore the effects of interspecific variation in plant traits on soil C dynamics in the very early stages of stand development (9 years since planting). Mineral soil C stocks to 5 cm depth were quantified in monospecific plots of 19 tree species planted on a former agricultural field, and analyzed in relation to tree growth and functional traits. We found that tree species identity affected soil bulk density and, to a lesser extent, the carbon content of the topsoil, and thereby total C pools. Among species and across plots, mineral soil C stocks were positively correlated with rates of tree growth and were significantly larger beneath broadleaf trees with “fast” functional traits vs. conifers with more conservative leaf traits, when comparisons were made over equivalent soil depth increments. Thus, plant functional traits mediate interspecific differences in productivity, which in turn influence the magnitude of belowground C stocks. These results highlight important linkages between above- and belowground carbon cycles in the earliest stages of afforestation.